(untitled) (Research, Society and Development, 2022)
The objective of the present study was the elaboration, physical characterization and calculation of the nutritional value of a muffin-type cake with the addition of in natura cabotiá pumpkin pulp and rind with cumbaru nut. Standard muffins (M.P) were formulated plain, flavorless. On the basis of 100% of the M.P, 15% (MI) and 45% (MII) of grated in natura pumpkin with pulp and peel were added to the raw dough. Cumbaru nuts were placed in the three formulations. The moisture content, ash, yield and calculation of nutritional value were evaluated. The moisture results for M.P was 20.95%, M.I 26.48% and M.II 36.48. The values of analysis of mineral residues (ash) were 5.13% for M.P, 4.56% M.I and 4.12% M.II. With regard to the yield obtained, they were 82.09%, 83.93% and 85.39% for the M.P, M.I and M.II formulations respectively. The energetic value of the M.P formulation was 351 Kcal, M.I 312 Kcal and M.II 257 Kcal. It is concluded that it was possible to prepare and obtain the muffin-type cake, from the two formulations that were added to the pumpkin peel and pulp, maintaining the softness and reducing the energy value compared to the muffins taken as standard.